2021
DOI: 10.1177/00333549211018675
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Racism and Vigilance During the COVID-19 Pandemic: Mental Health Implications Among Asian and Black Americans

Abstract: Objectives Experiences of vicarious racism—hearing about racism directed toward one’s racial group or racist acts committed against other racial group members—and vigilance about racial discrimination have been salient during the COVID-19 pandemic. This study examined vicarious racism and vigilance in relation to symptoms of depression and anxiety among Asian and Black Americans. Methods We used data from a cross-sectional study of 604 Asian American and 844 Black American adults aged ≥18 in the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
160
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 76 publications
12
160
1
Order By: Relevance
“…Drawing on survey data from 209 Asians residing in the United States, the study presents the findings consistent with earlier research [20,21] showing that experience of racial discrimination induced by the COVID-19 pandemic was negatively related to the well-being among Asian people. Effective interventions should be designed to provide timely assistance to Asians who have experienced discrimination during the pandemic to prevent them from developing further depressive symptoms.…”
Section: Principal Findingssupporting
confidence: 83%
See 3 more Smart Citations
“…Drawing on survey data from 209 Asians residing in the United States, the study presents the findings consistent with earlier research [20,21] showing that experience of racial discrimination induced by the COVID-19 pandemic was negatively related to the well-being among Asian people. Effective interventions should be designed to provide timely assistance to Asians who have experienced discrimination during the pandemic to prevent them from developing further depressive symptoms.…”
Section: Principal Findingssupporting
confidence: 83%
“…It is worthwhile to examine the two constructs' unique relationship with depression, as previous literature suggested that the two might have different psychological implications. Although experienced discrimination was consistently associated with poor well-being [20,21], the role of worry seemed less conclusive. Worry is a normal mental reaction to impending events in our lives, and it only poses a threat when it becomes persistent and less controllable [25,26].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, the number of hate crimes in the U.S. during 2020 reported by FBI was the highest since 2008 (11). Direct and vicarious forms of racial/ethnic discrimination during the pandemic have been found to be positively associated with decreased mental health among racial/ethnic minority adults (12)(13)(14)(15). A recent study involving a national sample of Asian, Black, Indigenous, and Latinx young adults ages 18-25 found the majority of respondents reported at least one instance of COVID-related victimization and when controlling for pre-existing COVID-19 medical risks and financial insecurity, perceptions that the coronavirus has increased racial bias across the country mediated the positive association between coronavirus victimization distress and depression and anxiety (16).…”
Section: Introductionmentioning
confidence: 99%